Utility of population-based HIV impact assessments to understand the associations of stigma with the HIV treatment cascade: Analytical framework using cross-sectional evidence from Tanzania. - Mohamed F Jalloh; Alexander Kailembo; Nicolas Schaad; Sophia A Nur; Prosper Njau; Haruka Maruyama; Kayla Lavilla; Kathy Hageman; Mbaraka Amuri; Nora Hennesy; Eunice Mmari; Mahesh Swaminathan; et al. (PLoS ONE)
Background Stigma is a major barrier to ending HIV as a public health threat. We present an analytical framework for quantifying the effects of HIV-related stigma on the treatment cascade using biomarker data from a Population-based HIV Impact Assessment (PHIA) in Tanzania. Methods We first reviewed HIV-related stigma items from 15 PHIA surveys in sub-Saharan Africa. Using nationally representative data of 1,831 diagnosed and undiagnosed PLHIV aged 15 and older in Tanzania, we applied modified Poisson regression models to examine associations of stigma with the treatment cascade, adjusting for HIV knowledge and demographics. Results We identified 41 unique stigma-related items in 13 of the 15 PHIA surveys. In Tanzania, PLHIV who expressed any stigma driver (stigmatizing attitude, discriminatory attitude, or shame) were 27% less likely to know their HIV status (adjusted prevalence ratio [aPR] 0.73; 95%CI [0.65-0.83], p < 0.001), while those expressing all three were almost never aware of their status (aPR < 0.01; 95%CI [0-0.01], p < 0.001). Stigma drivers were not significantly associated with ART use among diagnosed PLHIV or viral load suppression (VLS) among those on ART. Diagnosed PLHIV who felt the need to hide their status when seeking non-HIV healthcare were 9% less likely to be on ART (aPR 0.91; 95%CI [0.85-0.98], p = 0.013), and those on ART were 10% less likely to achieve VLS (aPR 0.90; 95%CI [0.81-0.99], p = 0.047). Conclusions Stigma likely prevented many undiagnosed PLHIV in Tanzania from knowing their status. Fear of healthcare discrimination due to anticipated stigma undermines ART uptake among diagnosed PLHIV and viral suppression among those on ART. PHIA surveys have untapped potential to quantify the effects of HIV-related stigma and inform interventions to end HIV as a public health threat.